PENGEMBANGAN ALGORITMA MOW DAN GENERALISASI BAHASA AUTOMATA UNTUK PROSES PEMBUATAN MINUMAN SERTA PENGEMBALIAN UANG PADA DESAIN MESIN KOPI OTOMATIS - Wamiliana Wamiliana; Ossy Dwi Endah Wulandari; Marisa Ayu Rahmadhani (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
The remarkably development in science and technology influences the business trend. One of the mode of businesses that are used widely nowadays is vending machine. Vending machine is a machine that is able to serve client for food, drink and others after the costumers put money into machine slot. This research discusses about an application of coffee vending machine that can make variation of coffee and optimalize output of the money. In making this application, Finite State Automata (FSA) is applied to handle the problem for recognize language in making a drink and MOW algorithm used to optimalize output of money in transaction processing. Keywords : Coffee Vending Machine, Finite State Automata, Optimalize, Algorithm